Laser celaning process for the removal of surface contaminants, corrosion and paint - Ramasamy, Linggamm; Quazi, Moinuddin Mohammed; Aiman, M.H.; Mahadzir, Ishak (2021)
Laser cleaning is an ideal technology that replace conventional chemical technique for coating removal process. This unique technique can remove coating layer without defect the metal substrate surface. Laser cleaning process can be use in many industrial application such as Automotive industries and petrochemical industires. Archaeological sites of restoration possible with laser cleaning